2022
DOI: 10.1016/j.ajog.2021.08.004
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of low-dose aspirin for the prevention of preeclampsia in women at high risk in China

Abstract: BACKGROUND: Low-dose aspirin has been the most widely studied preventive drug for preeclampsia. However, guidelines differ considerably from country to country regarding the prophylactic use of aspirin for preeclampsia. There is limited evidence from large trials to determine the effect of 100 mg of aspirin for preeclampsia screening in women with high-risk pregnancies, based on maternal risk factors, and to guide the use of low-dose aspirin in preeclampsia prevention in China. OBJECTIVE: The Low-Dose Aspirin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 50 publications
1
35
1
1
Order By: Relevance
“…The results of this study are consistent with the findings of investigations conducted by other researchers (Asmare et al, 2018;Girma et al, 2019). Women who had severe pregnancy-induced hypertension without proteinuria had a higher rate of low birth weight, according to the findings of a multicenter trial that investigated the role of aspirin in the prevention of eclampsia (Lin et al, 2022). Normotensive mothers and those with mild hypertension had the lowest risk of having a baby with a low birth weight.…”
Section: Resultssupporting
confidence: 91%
“…The results of this study are consistent with the findings of investigations conducted by other researchers (Asmare et al, 2018;Girma et al, 2019). Women who had severe pregnancy-induced hypertension without proteinuria had a higher rate of low birth weight, according to the findings of a multicenter trial that investigated the role of aspirin in the prevention of eclampsia (Lin et al, 2022). Normotensive mothers and those with mild hypertension had the lowest risk of having a baby with a low birth weight.…”
Section: Resultssupporting
confidence: 91%
“…Early (gestational age <16 weeks) initiation with low-dose aspirin (<300 mg) effectively reduced early-onset preeclampsia by transforming the spiral arterioles during early placentation and reducing blood resistance. 11–15 Contrary to most studies, a recent randomized controlled trial did not find a reduction in preeclampsia in a Chinese cohort, 19 which might be attributed to a wider range of initiation of low-dose aspirin (12–20 gestational age). The other proven benefits of low-dose aspirin administered in early pregnancy are the prevention of intrauterine growth restriction and preterm birth, which has been a routine practice in most institutions.…”
Section: Introductionmentioning
confidence: 85%
“…In Asian women, the dose-dependent efficacy of low-dose aspirin [ 79 ] and its efficacy in women with blood pressure of 130–139/80–89 mmHg, which is included in the American College of Cardiology/American Heart Association definition of Stage 1 hypertension or mild hypertension [ 80 ], have also been reported. However, a study reported that aspirin has poor efficacy when started at 12–20 weeks gestation [ 81 ]. The ADA guidelines also strongly recommended aspirin for women with diabetic pregnancies until 2020 [ 82 ]; moreover, the recommendations became weaker in the 2021 edition and later editions [ 83 ].…”
Section: Prediction Prevention and Treatmentmentioning
confidence: 99%